Effect of Boron Distribution on the Intergranular Corrosion Resistance of UNS S32506 Duplex Stainless Steels. Issue 13 (14th August 2019) - Takei, Takayuki; Yabe, Murotsune; Ooi, Azusa; Tada, Eiji; Nishikata, Atsushi
Abstract : The effect of boron distribution on the intergranular corrosion (IGC) resistance of UNS S32506 duplex stainless steel (DSSs) was investigated. IGC tests in boiling nitric acid were conducted with DSSs with boron contents ranging from 1 to 50 ppm. The corrosion rate increased with increasing boron addition. Further addition of boron did not affect the IGC resistance. Microstructural observations, corrosion depth measurements, and secondary-ion mass spectrometry analysis revealed that the diminished IGC resistance was attributable to corrosion resistance degradation of α/γ interfaces due to boron segregation at the interfaces.